The Effect Of Supervisory Supervision And Emotional Intelligence On The Performance Of The Head Of A Private Junior High School In Bogor Regency - Taty Rahayuningsih (International Journal of Management, Innovation, and Education, 2022)
This study aims to determine the strength of variables that allegedly affect the performance of school principals. These variables are supervise supervisors, and emotional intelligence that allegedly can affect the performance of the principal. The population of this study was 390 principals of private junior high schools in Bogor district. The sampling technique uses Multistage Randam Sampling, with the Taro Yamane formula  with 198 samples. The results of the study found that 1) the hypothesis of  Supervising Supervision (X1) on Principal Performance (Y) resulted  in a path coefficient of 0.173 by providing positive direct effect conclusions, 2) the hypothesis of Emotional Intelligence (X2) on Head Performance (Y) produced a path coefficient of 0.125 by providing positive direct    effect conclusions .  The results of the SITOREM analysis show that there are  10 indicators from 2 variables that must be improved immediately and 2 indicators from 3 variables maintained or developed.